2010
DOI: 10.1097/hco.0b013e32833f0461
|View full text |Cite
|
Sign up to set email alerts
|

Choice of initial medical therapy vs. prompt coronary revascularization in patients with type 2 diabetes and stable ischemic coronary disease with special emphasis on the BARI 2D trial results

Abstract: In many patients with type 2 diabetes and stable CAD in whom angina symptoms are controlled, OMT alone should be the first-line strategy. In patients with more extensive coronary disease, prompt CABG, in the absence of contraindications, OMT, and an insulin sensitization strategy are a preferred therapeutic strategy to reduce the incidence of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…One of the most effective treatments for reducing symptoms of angina is revascularization [14]. Several randomized trials, however, have demonstrated that revascularization does not improve the mortality in patients with stable chronic angina [1519]. In a recently published meta-analysis of 10 prospective randomized controlled trials with a total of 6752 patients, no differences between percutaneous coronary intervention (PCI) versus medical therapy for all-cause mortality, cardiovascular mortality, angina relief at the end of follow-up were noted.…”
Section: Management Of Angina – Basic Principles and Traditional Tmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most effective treatments for reducing symptoms of angina is revascularization [14]. Several randomized trials, however, have demonstrated that revascularization does not improve the mortality in patients with stable chronic angina [1519]. In a recently published meta-analysis of 10 prospective randomized controlled trials with a total of 6752 patients, no differences between percutaneous coronary intervention (PCI) versus medical therapy for all-cause mortality, cardiovascular mortality, angina relief at the end of follow-up were noted.…”
Section: Management Of Angina – Basic Principles and Traditional Tmentioning
confidence: 99%
“…PCI was not associated with reductions in all-cause or cardiovascular mortality, myocardial infarction (MI), or angina relief [20]. Surgical revascularization was in fact superior to percutaneous revascularization (BARI2D and FREEDOM) in reducing the death and MI in patients with diabetes [1719, 21] and those with severe left main, proximal LAD disease or high syntax score (SYNTAX) [22]. These findings continue to support existing clinical practice guidelines that medical therapy be considered the most appropriate initial clinical management for patients with stable angina.…”
Section: Management Of Angina – Basic Principles and Traditional Tmentioning
confidence: 99%